Drug prescribing patterns in geriatric patients in selected health facilities of Addis Ababa, Ethiopia - Wegayehu Lemma&, Mojahidul Islam, Eskindir Loha, Vijender Singh Mahalwal (Journal of Applied Pharmaceutical Science, 2020)
Drug prescribing for geriatric patients is a complex and challenging process because of age-related physiological changes. The drug prescriber plays a critical role in identifying drugs use within the community and improving drug therapy is the most important intervention in the elderly. The aim of the study was to evaluate the patterns of drug prescribing in elderly patients attending selected healthcare facilities in Addis Ababa, Ethiopia, by means of World Health Organization’s (WHOs) prescribing and health facility assessment tools. The study design used was retrospective for assessing prescribing patterns and prospective methods to evaluate healthcare facilities. Data were collected in Ethiopia from April 20 to August 20, 2019. Retrospectively, 1,200 prescriptions were analyzed according to WHO guidelines. The mean number of drugs per encounter varied from 2.2 to 2.67, the percentage of drugs prescribed by generic name ranged from 436(81.95%) to 919(91.62%), the percentage of prescriptions with injections ranged from 65(16.25%) to 68(34%), and the percentage of drugs prescribed from the Ethiopian essential drug list (EDL) varied from 407 (76.5%) to 918(91.53%). This prospective study showed that in healthcare facilities the percentage availability of the copy of the Ethiopian EDL was 5(100%), standard treatment guideline was 4 (80%), drug formulary was 4 (80%), and none of the facilities had international prescribing guidelines. The methods of prescribing by generic name, prescribing drugs from the EDL, and polypharmacy were near-optimal with the standard WHO requirements. However, there is a need to improve the pattern of prescribing antibiotics and injection medicines, the availability of key essential medicines in the stock, and the availability and use of international guidelines, such as AGS Beers Criteria, which is a guide for decisions about what drugs to use in geriatric patients.
Keywords: Geriatric, health facility indicators, prescribing indicators.